2018
DOI: 10.5539/ibr.v11n6p151
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Effectiveness of National Enforcers in the IFRS Context: A Proactive Approach

Abstract: It is widely acknowledged that an effective enforcement system represents a crucial element to achieve significant improvements in financial reporting through the adoption of high-quality accounting standards. Indeed, the quality of financial reporting is considerably influenced not only by the standards to be adopted but also by their actual implementation, and consequently by enforcement mechanisms.The topic has generated considerable interest among scholars, who devoted their attention to developing differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…It has been documented that high AQ likely to restrict EM and the FRQ has been used to measure such opportunistic behavior, for example, the discretionary accruals (Jones, 1991), timely loss recognition (Basu, 1997) and accruals quality measure (Dechow & Dichev, 2002). A close review has indicated mixed outcomes like mandatorily IFRS implementation has improved the AQ in majority of the countries (Jung et al, 2016; Kim et al, 2012; Quagli et al, 2018); per contra few studies have conceded significant decrease in the AQ (Barth et al, 2008; Liu et al, 2011); while others could not traced any evidence of impacts of IFRS in the AQ (Laili & Kahari, 2013). Literature has also painted that a decreased emphasis on the verifiability, a pivotal concept in the IFRS implementation probably has led to relatively less specific and less prescriptive guidance and has increased subjectivity in the accounting measurement (Jamal et al, 2010), leading to litigation risk and higher audit risk (Diehl, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been documented that high AQ likely to restrict EM and the FRQ has been used to measure such opportunistic behavior, for example, the discretionary accruals (Jones, 1991), timely loss recognition (Basu, 1997) and accruals quality measure (Dechow & Dichev, 2002). A close review has indicated mixed outcomes like mandatorily IFRS implementation has improved the AQ in majority of the countries (Jung et al, 2016; Kim et al, 2012; Quagli et al, 2018); per contra few studies have conceded significant decrease in the AQ (Barth et al, 2008; Liu et al, 2011); while others could not traced any evidence of impacts of IFRS in the AQ (Laili & Kahari, 2013). Literature has also painted that a decreased emphasis on the verifiability, a pivotal concept in the IFRS implementation probably has led to relatively less specific and less prescriptive guidance and has increased subjectivity in the accounting measurement (Jamal et al, 2010), leading to litigation risk and higher audit risk (Diehl, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of the implementation of IFRS have primarily indicated an improvement in the explanatory power of accounting figures (Iatridis, 2010;Salameh, 2013) and in transparency (Ahmed et al, 2013), and has aided in relatively smoother information flow (Trebelsi, 2018). Furthermore, reduction in the costs of capital (Merino et al, 2014), reductions in earnings management (EM) (Jude & Felix, 2017), improvements in audit quality (AQ) (Quagli et al, 2018), reduction in audit fees (Kim et al, 2012), better forecasting accuracy with reduced forecasting errors (Neel, 2017) and even reductions in tax liability (Ya pa et al, 2015) have been suggested in the extant literature.…”
Section: Introductionmentioning
confidence: 99%
“…The term ‘Audit quality’ (AQ) in accounting literature refers to the seminal definition as proposed by DeAngelo, (1981) as ‘the market assessed joint probability that a given auditor will both (a) discover a breach in the client’s accounting system, and (b) report the breach’. Documented literature reveals that mandatorily adopted IFRS have improved the AQ in most countries (Quagli et al, 2018), differing with few studies, while others have concluded without any such precedence.…”
Section: The Settingmentioning
confidence: 98%
“…Preiato, Brown, and Tarca compare between-country measures of legal setting and enforcement of accounting standards, offering insights into variations in regulatory environments and their implications for financial reporting quality and enforcement mechanisms within regional and international contexts [18]. Quagli, Avallone, Ramassa, and Di Fabio [19] and Quagli, Avallone, Ramassa, and Motta [20] explore the effectiveness of national enforcers in the IFRS context, investigating the role of regulatory agencies in ensuring compliance with accounting standards and promoting transparency and accountability within regional jurisdictions.…”
Section: The Utilization Of International Financial Reporting Standardsmentioning
confidence: 99%